EXPLORING THE ROLE OF PORTFOLIOS IN FOSTERING STUDENT COURSE ENGAGEMENT - Cimermanova, Ivana; Jelavic, Dajana (Advanced Education, 2024)
Reflective learning is an important factor that has a positive impact on students’ learning efficacy. The study aims to bring insight into the use of e-portfolios as a means and tool to promote reflection in the classroom and build self-reflection habits, plan learning activities and build learning autonomy. Mahara e-portfolio was used during the period of eight months with a group of secondary school students in Croatia (n = 57) who filled in the student course engagement questionnaire consisting of 23 Likert-scale items before and after this period. The questionnaire data are categorized into four categories, dimensions: skills engagement, participation/ interaction engagement, emotional engagement and performance engagement. Students systematically worked with Mahara, and based on the data collected that were analysed using Statistica software, no positive impact on students’ engagement was proved. Even though the quantitative results are relatively neutral, the observations and discussions with teachers and students indicate a positive impact on motivation. Building autonomy and using tools for reflection and self-reflection should become necessary components of university pre-service teacher education.